Acute gastric perforation after leaving against medical advice: A case presentation. (February 2022) - Weinstein, David; Moran, Vicki; Culhane, John
Abstract: Introduction: Gastric perforation with necrosis is rare following acute gastric dilation (AGD) and can be fatal. We present a case of a patient with AGD due to a binge-eating episode who left the emergency department (ED) against medical advice (AMA) only to return with gastric perforation and necrosis requiring total splenectomy and partial gastrectomy. Case: A 28-year-old female without a remarkable past medical history presented to the ED with diffuse abdominal pain and obstipation after a three-day "food crawl." On admission, a computerized tomography (CT) scan revealed a markedly dilated stomach from the diaphragm to the pelvis with severe mass effect. The therapeutic plan at the time was gastric decompression via a nasogastric tube. The following day, the patient reported feeling better and left AMA only to return the same evening with worsening symptoms and peritoneal signs. The patient was then emergently taken to the operating room (OR). In the OR, laparotomy revealed frank spillage of partially digested food and necrosis along the greater curvature of the stomach that extended to the spleen. Damage control surgery was performed, which required a total splenectomy and a partial gastrectomy. The patient was admitted to the intensive care unit (ICU) and subsequently underwent five more trips to the OR due to severe edema that delayed the primary closure of the fascia. Once the patient was transferred out of the ICU, she was evaluated by psychiatry and diagnosed with a binge-eating disorder. Conclusion: This case demonstrates the severity of acute gastric dilation and its potentially lethal consequences. In some cases, such as this one, the patient may present with mild symptoms and not comprehend the gravity of the situation. Therefore, it is important for clinicians to recognize this condition as a true emergency and perform immediate decompression and evaluation for surgery.